Correlation between photoluminescence and Fourier transform infrared spectra in tetra-ethyl-ortho-silicate thin films - Choi, WC; Kim, TG; Kim, JS (IOP PUBLISHING LTD, 2006)
We report strong visible photoluminescence (PL) from thermally treated tetra-ethyl-ortho-silicate (TEOS) thin films at room temperature. High-resolution transmission electron microscope (HRTEM) studies showed that the PL originated from nanocrystalline-Si (nc-Si). HRTEM images showed that as-grown TEOS thin films had quasi-static amorphous (QSA) SiO2 phases instead of the typical amorphous (TA) SiO2 phases, and that they divided into small pieces of nc-Si after thermal treatment. In addition, Fourier transform infrared (FTIR) investigations showed that the QSA-SiO2 phases were composed of three types of bonding modes (i.e., Si-O-Si bending, Si-O bending, and Si-O-Si stretching), which play important roles in the formation of the nc-Si at relatively lower annealing temperatures.
Keywords: SI; LUMINESCENCE